Alterações induzidas pela toxina A do Clostridium difficile na via WNT/B-catenina in vivo e papel do RAC-1 na sua inibição em células epiteliais intestinais - Martins, Conceição da Silva (2018)
Clostridium difficile, an agent that causes diarrhea and colitis, produces toxin A (TcdA) and B, two potent enterotoxins. Both toxins reduce proliferation and apoptosis in intestinal epithelial cells. The Wnt-β-catenin pathway, when activated, stimulates the proliferation and differentiation of epithelial cells. In vitro, Clostridium difficile TcdA of has been shown to inhibit the Wnt/β-catenin pathway, even in the presence of pathway agonists. TcdA, as well as toxin B, inactivate Rho GTPases, including Rac1. Rac1 has an important role in the translocation of β-catenin to the nucleus, which stimulates the transcription of genes involved in cell proliferation. Therefore, the objective of this study was to evaluate the changes induced by the Clostridium difficile TcdA in the Wnt/β-catenin pathway in mice and to investigate the role of Rac-1 in the inhibitory activity of this toxin in the Wnt/β-catenin pathway in vitro. TcdA of Clostridium difficile (10 or 50μg/loop) or PBS (200 μl; control) were injeted on the ileal loop of C57BL/6 and Swiss mice. The animals were euthanized under anesthesia 4h later and segments of the ileum were collected to perform the histopathological analysis and to evaluate the components of the Wnt / β-catenin pathway by immunohistochemistry (β-catenin and Wnt-3a and ciclina), Western Blotting (β-catenin) and RT-qPCR (LGR5, cMYC, cyclin D1 and Wnt-3a), cell proliferation (by immunohistochemistry for Ki67 and cyclin D1) and Rac1 expression by RT-qPCR. Mouse intestinal epithelial cells (IEC-6) were transfected with pcDNA3-EGFP-Rac1-Q61L or pcDNA3 and incubated with TcdA (50 ng/ml) in the presence or absence of Wnt-3a conditioned medium. After 24h incubation, the activation of the Wnt/β-catenin pathway (through the TOP/FOPflash luciferase assay), nuclear β-catenin translocation by immunofluorescence and cell proliferation (immunocytochemistry for Ki67) wasevaluated. In vivo, TcdA of C.diff induced marked destruction of intestinal villi and intense inflammatory cell infiltration in the ileum tissue of both species. In the ileum of Swiss mice, the TcdA of Clostridium difficile increased the protein expression of β-catenin and reduced the gene expression of cyclin D1, while in the C57BL/6 mice, this toxin reduced β-catenin and cMYC gene expression, as well as increased gene expression of Wnt-3a and LGR5. In addition, TcdA decreased cell proliferation in the intestinal crypts and did not alter the expression of Rac1 in the ileum of both species. In intestinal epithelial cells (IEC-6), TcdA decreased the activation of the Wnt-β-catenin pathway by the pathway agonist (Wnt-3a), reduced β-catenin translocation to the nucleus and decreased proliferation, while transfection of IEC-6 with pcDNA3-EGFP-Rac1-Q61L reversed the TcdA of Clostridium difficile effects in the presence of Wnt-3a. We conclude that TcdA of Clostridium difficile inhibits the Wnt/β-catenin pathway in Swiss and C57BL/6 mice, despite the increasing level of endogenous agonist of the pathway, with the main altered genes being those involved in cell proliferation. In addition, the in vitro results show an important role of Rac1 inactivation by TcdA of Clostridium difficile in the Wnt/β-catenin pathway inhibition.